1999
DOI: 10.1128/jb.181.20.6300-6305.1999
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MexT, the Regulator of the MexE-MexF-OprN Multidrug Efflux System of Pseudomonas aeruginosa

Abstract: We investigated the regulation of the MexEF-OprN multidrug efflux system of Pseudomonas aeruginosa, which is overexpressed innfxC-type mutants and confers resistance to quinolones, chloramphenicol and trimethoprim. Sequencing of the DNA region upstream of the mexEF-oprN operon revealed the presence of an open reading frame (ORF) of 304 amino acids encoding a LysR-type transcriptional activator, termed MexT. By using T7-polymerase, a 34-kDa protein was expressed in Escherichia coli from a plasmid carrying the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(144 citation statements)
references
References 42 publications
8
133
0
3
Order By: Relevance
“…These mexT genes were unimpaired because KH4014a-vmexT transformed with mexT(8380) exhibited the nfxC-phenotype (Table 3). The results are consistent with the sequence analysis of mexT in the nfxC-type mutant derived from PAO1-Geneva suggesting that the nfxCtype mutant must have an additional mutation as indicated previously [14].…”
Section: Sequence Of Mext In 8380 and 1008supporting
confidence: 91%
“…These mexT genes were unimpaired because KH4014a-vmexT transformed with mexT(8380) exhibited the nfxC-phenotype (Table 3). The results are consistent with the sequence analysis of mexT in the nfxC-type mutant derived from PAO1-Geneva suggesting that the nfxCtype mutant must have an additional mutation as indicated previously [14].…”
Section: Sequence Of Mext In 8380 and 1008supporting
confidence: 91%
“…This efflux pump, which can extrude fluoroquinolones, chloramphenicol, trimethoprim and tetracycline (Vila and Martínez, 2008), has a particular genetic structure: upstream from the mexE there is no repressor gene transcribed divergently, but there is an ORF, called mexT, encoding a protein, which belongs to the LysR family of transcriptional activators, and is transcribed in the same direction as the other three genes. MexT is essential for the mexEF-oprN activation (Kohler et al, 1999). In addition, adjacent to and activated by mexT is a further gene, transcribed divergently, termed mexS [previously qrh (Kohler et al, 1999)], which does encode a regulatory protein, as it is, in fact, an oxidoreductase, but can confer the MAR phenotype by enhancement of MexEF-OprN overexpression (Sobel et al, 2005b).…”
Section: Chromosome-mediated Quinolone Resistancementioning
confidence: 99%
“…MexT is essential for the mexEF-oprN activation (Kohler et al, 1999). In addition, adjacent to and activated by mexT is a further gene, transcribed divergently, termed mexS [previously qrh (Kohler et al, 1999)], which does encode a regulatory protein, as it is, in fact, an oxidoreductase, but can confer the MAR phenotype by enhancement of MexEF-OprN overexpression (Sobel et al, 2005b). The mexEF-oprN is not expressed under standard growth in laboratory conditions.…”
Section: Chromosome-mediated Quinolone Resistancementioning
confidence: 99%
“…We therefore suspect that, in these two isolates, loss of OprD was caused by an OprD repression mechanism acting at the post-transcriptional level. Recently, Köhler et al (1999) showed that co-regulation of OprD and the MexEF-OprN efflux system occurred at the transcriptional but also at the post-transcriptional level. Ochs et al (1999) also suggested that OprD is influenced by more than one mechanism of repression.…”
Section: Expression Of Oprdmentioning
confidence: 99%